2014
DOI: 10.1103/physrevb.89.064403
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of two-dimensional antiferromagnetism with temperature and magnetic field in multiferroicBa2CoGe2O7

Abstract: We report on spherical neutron polarimetry and unpolarized neutron diffraction in zero magnetic field as well as flipping ratio and static magnetization measurements in high magnetic fields on the multiferroic square lattice antiferromagnet Ba 2 CoGe 2 O 7 . We found that in zero magnetic field the magnetic space group is Cm m2 with sublattice magnetization parallel to the [100] axis of this orthorhombic setting. The spin canting has been found to be smaller than 0.2 • in the ground state. This assignment is i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 40 publications
6
26
0
Order By: Relevance
“…The associated spin shortening is S ≈ 1.3 to 1.35, about 10% of the full spin value of 3/2 -the magnetization at the saturation field is about 10% smaller from the fully saturated value in very high magnetic field [24]. In comparison, the spin shortening in SCGO is S = 1.491, less than 1%.…”
Section: Comparison To Ba2coge2o7mentioning
confidence: 85%
See 1 more Smart Citation
“…The associated spin shortening is S ≈ 1.3 to 1.35, about 10% of the full spin value of 3/2 -the magnetization at the saturation field is about 10% smaller from the fully saturated value in very high magnetic field [24]. In comparison, the spin shortening in SCGO is S = 1.491, less than 1%.…”
Section: Comparison To Ba2coge2o7mentioning
confidence: 85%
“…The magnetization curves are nearly isotropic, and the difference in the saturation fields is mainly explained by the g-tensor anisotropy. In otheråkermanite compounds, like Sr 2 CoSi 2 O 7 [8] and Ba 2 CoGe 2 O 7 [24], the slope of in-plane magnetization is almost twice the slope of the magnetization measured perpendicular to the cobalt plane. This large difference signals the presence of large easy-plane anisotropy.…”
Section: A Magnetizationmentioning
confidence: 97%
“…Earlier studies of BCGO suggested a tetragonal crystal symmetry, and thus the fourfold or U(1) symmetry for describing the in-plane magnetization 26,28 . However, recent detailed investigations indeed revealed the presence of the twofold magnetization in the plane and an orthorhombic Cm 0 m2 0 magnetic space group 30,31 . The twofold symmetry is likely to be reinforced by the small but unavoidable in-plane magnetic field component, coming from the tilting of the magnetic field from the c-axis.…”
Section: Discussionmentioning
confidence: 99%
“…1), inelastic neutron diffraction 28 , electron spin resonance and far infrared spectroscopy 29 . However, recent studies on the lattice and magnetic structure 30,31 show that BCGO actually has a lower symmetry with weak orthorhombic distortion in the plane and result in magnetic space group Cm 0 m2 0 . A change in the FE polarization appears below the AF ordering temperature (T N ¼ 6.7 K, Supplementary Fig.…”
mentioning
confidence: 99%
“…In Ba 2 CoGe 2 O 7 , the room temperature crystal structure is indeed tetragonal P42 1 m with a = b ≈ 8.39Å and c ≈ 5.56Å (Ref. [11]), with possible symmetry lowering to orthorhombic Cmm2 at low temperatures [11,12]. The room temperature crystal structure of Sr 2 CoSi 2 O 7 is also tetragonal P42 1 m with a = b ≈ 8.03Å and c ≈ 5.16Å (Ref.…”
Section: With Antiferromagnetic Order Along the [100] Or [010] Axes Fmentioning
confidence: 97%